[Ni(NHC)2] as a Scaffold for Structurally Characterized trans [H−Ni−PR2] and trans [R2P−Ni−PR2] Complexes. Issue 52 (4th August 2021) - Sabater, Sara; Schmidt, David; Schmidt, Heidi (née Schneider); Kuntze‐Fechner, Maximilian W.; Zell, Thomas; Isaac, Connie J.; Rajabi, Nasir A.; Grieve, Harry; Blackaby, William J. M.; Lowe, John P.; Macgregor, Stuart A.; Mahon, Mary F.; et al.
Abstract: The addition of PPh2 H, PPhMeH, PPhH2, P( para ‐Tol)H2, PMesH2 and PH3 to the two‐coordinate Ni 0 N‐heterocyclic carbene species [Ni(NHC)2 ] (NHC=I i Pr2, IMe4, IEt2 Me2 ) affords a series of mononuclear, terminal phosphido nickel complexes. Structural characterisation of nine of these compounds shows that they have unusual trans [H−Ni−PR2 ] or novel trans [R2 P−Ni−PR2 ] geometries. The bis‐phosphido complexes are more accessible when smaller NHCs (IMe4 >IEt2 Me2 >I i Pr2 ) and phosphines are employed. P−P activation of the diphosphines R2 P−PR2 (R2 =Ph2, PhMe) provides an alternative route to some of the [Ni(NHC)2 (PR2 )2 ] complexes. DFT calculations capture these trends with P−H bond activation proceeding from unconventional phosphine adducts in which the H substituent bridges the Ni−P bond. P−P bond activation from [Ni(NHC)2 (Ph2 P−PPh2 )] adducts proceeds with computed barriers below 10 kcal mol −1 . The ability of the [Ni(NHC)2 ] moiety to afford isolable terminal phosphido products reflects the stability of the Ni−NHC bond that prevents ligand dissociation and onward reaction. Abstract : Whole lotta terminal phosphidos : A combined experimental and computational study of the reactivity of [Ni(NHC)2 ] (NHC=N‐heterocyclic carbene) towards secondary and primary phosphines has been undertaken. P−H bond activation, as well as P−P activation of diphosphines, yields an extensive series of structurally characterised terminal phosphido complexes that exhibit unusual trans ‐phosphido hydrido and novel trans ‐bis‐phosphido geometries.